Platform-based sustainable business models: reducing food waste in food services. (7th July 2020) - Mattila, Malla; Mesiranta, Nina; Heikkinen, Anna
Food waste is a growing sustainability challenge for companies operating in the food services sector in developed countries. In this study, we examine how platform-based business models for food waste reduction can contribute to sustainability. We draw from the literature on business sustainability, sustainable business models (SBMs), and digital platforms, scrutinising two real-life business cases that provide digital services that help food service companies to reduce their food waste. Our findings identify the value network (user, producer, and support networks) and sustainable value proposition (economic, environmental, and social dimensions) as key elements for addressing sustainability in platform-based businesses. The study contributes to the SBM literature by developing an empirical and systemic understanding of platform-based SBMs. The cases illustrate that these SBMs have the potential to contribute to sustainability through scalability and attractiveness. From a managerial standpoint, the study offers companies insights into how to develop sustainability in their business operations.